Comparative Transcriptome Analysis Reveals Related Regulatory Mechanisms of Androgenic Gland in Eriocheir sinensis. (9th November 2017) - Fu, Chunpeng; Zeng, Qifan; Li, Fajun; Wang, Huicui; Sun, Jian; Wang, Hui
Abstract : Chinese mitten crab (Eriocheir sinensis) is one of the most commercially important aquaculture species in China. The androgenic gland (AG) of crustaceans plays pivotal roles in the regulation of male differentiation and in maintaining the male sexual characteristics. In order to reveal related mechanisms in AG, we compared transcriptomes of AG between proliferation and secretion phase. A total of 72, 000 unigenes and 4, 027 differentially expressed genes were obtained. Gene ontology enrichment analysis indicated that biological processes and metabolic pathways related to protein synthesis and secretion such as transcription, translation, and signal transduction were significantly enriched. Critical genes such as IAG, SXL, TRA-2, SRY, FTZ-F1, FOXL2, and FEM-1 were identified and potentially involved in maintaining the testis development and spermatogenesis. Ribosomes pathway revealed the cause of insulin-like androgenic gland hormone secretion increase. Three insulin-like receptors were thought to be associated with growth and spermatogenesis. In the neuroactive ligand-receptor interaction pathway, the expression of octopamine receptor, 5-HT receptor 1, and melatonin receptor was significantly changed, which revealed the key regulation mechanism of aggressive and mating behavior of males. Comparative transcriptome analysis provided new insights into the genome-wide molecular mechanisms of AG development and the regulatory mechanisms of male development.